Analysis Of Configuration And Performance Of Arrester For Protecting Substation Against Impulse Lightning Using ATP-EMTP Software - Adri, Alfian; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Electrical energy is one of the most important and often used energy in life. Therefore to keep the availability of electricity, it takes a power company that will manage the electricity needs. One of the things that affect to the reliability of the equipment is need to know the configuration of the electrical equipment protective device. As known that transmission line is very vulnerable to lightning strikes that produce a traveling wave. It can enter the substation and make the existing equipment in danger. Based on the problems we need to analyze the configuration and performance of the arrester against the impulse lightning. This study was conducted by simulating lightning strikes on equipment using ATP-EMTP software by varying the strike and the distance of the arrester protection for protected transformer in order to get the correct distance to minimize the optimum voltage. The result of the simulation by varying the distance from 3 m, 6.7 m, 9 m, 15 m, 21 m, 27 m, 28.5 m, the safer distance and the smaller peak voltage which is protected by the arrester to the transformer is 21 meters from the current variation at 10 kA, 30 kA, and 60 kA where the lowest peak voltage of phases A, B, and C are compared with other distances. Then the distance 21 m better than the distance of 6.7 m used by PT.PLN (Persero) Garuda Sakti Substation.Keywords: Arrester, ATP-EMTP, Arrester configuration.